PENGARUH FINANCIAL RATIOS TERHADAP NILAI PERUSAHAAN - Subagio, Indra Sukma (LPPM Universitas Harapan Bangsa, 2023)
Firm value is one of the things considered by investors in investment decisions. Companies with a high value are expected to guarantee high dividends for investors. There are several factors that affect the high and low value of the company, some of which are financial ratios. This study aims to find out whether financial ratios can affect company value. Price to book value, current ratio, debt to equity ratio, and return on equity are used as proxies to measure firm value, liquidity, leverage, and profitability. Using 73 companies listed on the IDX in the financial sector in 2022 as a research sample, it was found that profitability has an effect on company value. Leverage also has a significant effect but in a negative direction and liquidity has no effect even though the direction is positive.